Integrasi Hadis dan Astronomi dalam Pengukuran Arah Kiblat: Pemberdayaan Literasi Syar'i-Saintifik pada Santri Pondok Pesantren As'ad Jambi - Baharudin Baharudin; Hafifatul Auliya Rahmy (Pusat Riset dan Inovasi Nasional, 2025)
The accuracy of qibla direction remains a significant challenge for Muslim communities, particularly in educational institutions where misconceptions about qibla measurement methods persist. This community service program addressed the need for accessible astronomical literacy among students at Pondok Pesantren As'ad Jambi by introducing protractor-based qibla measurement techniques. Implemented on November 11, 2023, the program engaged 90 participants comprising Madrasah Aliyah students and Ma'had Aly Ibrahimi students through an integrated approach combining theoretical exposition and hands-on practice. The intervention utilized a dual-method framework: interactive lectures elucidating Islamic jurisprudence and astronomical principles of qibla determination, followed by direct application of protractor measurement techniques. Evaluation through participant observation and post-activity assessment revealed substantial knowledge enhancement and practical skill acquisition among attendees. Participants demonstrated improved understanding of qibla direction concepts and gained confidence in applying measurement techniques independently. The program's success manifested in heightened enthusiasm for astronomy-based religious practices and increased capacity for autonomous qibla verification at household level. This initiative contributes to bridging traditional Islamic scholarship with contemporary scientific methodologies, fostering critical thinking in ritual observance while preserving religious authenticity.